METHODOLOGICAL FUNDAMENTALS OF ANALYZING THE EFFICIENCY FROM ITEMS OF THE CATEGORY "BEHAVIOR OF THE ENTERPRISE - KOSHOVYI, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article deals with the methodological and methodical principles of the analysis of the efficiency of the functioning of enterprises based on categories, criteria and indicators of behavior. The prospects of such an analysis from the point of view of building an ideal enterprise and considering the peculiarities of the development of market relations in Ukraine are highlighted.The essence of the concept of "enterprise behavior model" is substantiated. It was determined that the model of the efficiency of the enterprise's behavior can be built on the basis of the results of a detailed analysis of the prerequisites and factors that determine the peculiarities of the formation and manifestation of such behavior. It was established that the model of behavior as a universal category represents a certain algorithm of actions of an economic entity, which are predicted with a sufficient degree of probability, determined by the regularities of systemic relationships of cause and effect content.The model of the enterprise's behavior was typified according to the specified criteria, namely: the criterion of organizational culture, which includes ethical criteria, and the criterion of business activity, market orientation and the nature of the economic policy implemented by the enterprise. It is substantiated that the decision and algorithm of the company's actions as a result of the implementation of the model of their behavior can be made on the basis of simulation, expert and optimization models.It was determined that the achievement of the efficiency of the enterprise's development consists in the formation of a certain version of the enterprise's response in the coordinates of the maximum efficiency of the distribution of its resources, maintaining management control in accordance with the enterprise's development goals.
Keywords: enterprise behavior; efficiency; development; analysis; enterprise